Implementation of Tawhidi String Relations (TSR) on Household Consumption - Ari Susanto; Tatik Mariyanti (Indonesian Journal of Business, Accounting and Management (IJBAM), 2021)
In conventional economic theory, human needs are described as unlimited, while natural resources are limited. This concept breeds greed, and this is against Islam. In this paper, we will discuss consumption in Islam. The goal is to find the concept of consumption that brings benefits to humans. The study in this article is descriptive qualitative, using the Tawhidi String Relations (TSR) approach. Through the letter process or Interaction, Integrative, and Evolutions (IIE) a new understanding is created. The IIE process creates causal relationships as part of evolution. This study found a new form of understanding of the IIE process is the concept of consumption in Islam to achieve benefit. The benefit is oriented to the material (outward) and inner (reward).